English in Croatia today : opportunities for incidental vocabulary acquisition - Mihaljević-Djigunović, Jelena (Array, 2003)
The authors first look into the current status of the English language in the world and in Croatia. Starting from the fact that, in contrast to other foreign languages taught in Croatia, English distinguishes itself by the amount of exposure in everyday life, they carried out a study to see whether this exposure facilitates incidental vocabulary acquisition.